PENERAPAN NILAI QONA’AH UNTUK MEMBANGUN PENERIMAAN DIRI ANAK REMAJA YANG TINGGAL DI PANTI ASUHAN YA FATIMAH TAYU PATI - Sumi'ah; Komari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2022)
The application of qona'ah values is one of the efforts that can be carried out by the Ya Fatimah Tayu Pati Orphanage so that foster children can properly socialize, adapt to the environment in which they live, carry out routines well, and enjoy life, they must be able to apply these values qona'ah value in order to have a good attitude of self-acceptance from within oneself. This study aims to understand how to describe the application of qona'ah values and the self-acceptance of adolescents living in the Ya Fatimah Orphanage. This research is a type of field research. The subjects of this qualitative research were teenagers living in the Ya Fatimah Tayu Pati Orphanage. This research use desciptive qualitative approach. Observations, interviews, and documentation were used to obtain field data by researchers.The results of the study show that the application of qona'ah values to build selfacceptance among adolescents living in the Ya Fatimah Tayu Pati Orphanage includes, namely, accepting what is available willingly, asking God for additional additions that are appropriate and trying, accepting patiently on God's provisions, relying on God, not attracted by human deception. Teenagers who live in the Ya Fatimah Orphanage have good self-acceptance, namely, willingness to open up or express our various thoughts, feelings and reactions to others, psychological health, acceptance of others.